Look Who's Talking: Using creative, playful arts-based methods in research with young children. (March 2019) - Blaisdell, Caralyn; Arnott, Lorna; Wall, Kate; Robinson, Carol
Young children are often ignored or marginalised in the drive to address children's participation and their wider set of rights. This is the case generally in social research, as well as within the field of Arts-Based Education Research. This article contributes to the growing literature on young children's involvement in arts-based research, by providing a reflective account of our learning and playful engagement with children using creative methods. This small pilot project forms part of a larger international project titled Look Who's Talking: Eliciting the Voices of Children from Birth to Seven, led by Professor Kate Wall at the University of Strathclyde. Visiting one nursery in Scotland, we worked with approximately 30 children from 3 to 5 years old. Seeking to connect with their play-based nursery experiences, we invited children to participate in a range of arts-based activities including drawing, craft-making, sculpting, a themed 'play basket' with various props, puppetry and videography. In this article, we develop reflective, analytical stories of our successes and dilemmas in the project. We were keen to establish ways of working with children that centred their own creativity and play, shaped by the materials we provided but not directed by us. However, we struggled to balance our own agenda with the more open-ended methods we had used. We argue that an intergenerational approach to eliciting voice with young children – in which adults are not afraid to shape the agenda, but do so in responsive, gradual and sensitive ways – creates the potential for a more inclusive experience for children that also meets researcher needs.